Hubungan Struktur Biaya dengan Penciptaan Nilai Tambah pada Industri Makanan di Indonesia: Suatu Tinjauan Literatur - Mahmut, Cici; Charisma Ekawaty, Amri Amri, (YUME : Journal of Management, 2024)
An efficient cost structure in the food industry allows companies to create added value by optimizing expenses and increasing competitiveness and profit margins. This literature review aims to understand how each component in the cost structure including raw material costs, labor and overhead costs contributes to the creation of added value in the Indonesian food industry. This research was conducted through a systematic literature review that focuses on relevant studies and theories regarding cost structures and added value by selecting articles that focus on the food industry, relevant publications in the last 10 years. Analysis of the cost structure in the food industry shows that the management of various cost components, namely fixed, variable, semi-variable and other costs, plays a significant role in determining a company's profitability and competitiveness.Keywords : cost structure, added value, food industry, and literature review